Infinite vision : how Aravind became the world's greatest business case for compassion - Mehta, Pavithra K.; Shenoy, Suchitra (San Francisco, CA : Berrett-Koehler Publishers, 2012)
'The Aravind Eye Hospital, based in India, is the world's largest provider of high-quality eye care. It is also one of the world's most incredible and revolutionary organizations - delivering surgical outcomes equal to or exceeding those in the developed world at less than one percent of the cost, treating more than half of its patients free of charge, and taking no grants or donations. Aravind's success is so perplexing it has been the subject of a popular Harvard Business School case study. This is the first book to explore Aravind's history and the distinctive philosophies, practices, and commitments that are the keys to its success. Mehta and Shenoy share incredible stories about how Aravind grew from humble beginnings--founded by a retired ophthalmologist with no money or prior entrepre-neurial experience--to the world-class organization it is today. They explain the mysteries of a model that integrates innovation with empathy, service with business principles, and inner change with outer transformation. And they show how choices that seem foolish and unworkable can, when executed with compassion and integrity, yield powerful results - results that literally light the eyes of millions.'--Provided by publisher.
Includes bibliographical references and index.
Keywords: Aravind Eye Hospital (Madurai, India); Ophthalmology -- India -- History; Eye Diseases -- India -- Treatment; Health services accessibility -- India -- History